2019
DOI: 10.1113/jp278221
|View full text |Cite
|
Sign up to set email alerts
|

Housing temperature affects the acute and chronic metabolic adaptations to exercise in mice

Abstract: Mice are commonly housed at room temperatures below their thermoneutral zone meaning they are exposed to chronic thermal stress. r Endurance exercise induces browning and mitochondrial biogenesis in white adipose tissue of rodents, but there are conflicting reports of this phenomenon in humans. r We hypothesized that the ambient room temperature at which mice are housed could partially explain these discrepant reports between humans and rodents. r We housed mice at room temperature or thermoneutrality and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
74
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 91 publications
10
74
1
Order By: Relevance
“…Results of the GTT (Figure 1d) indicated a nonsignificant trend (p = .052) in glucose tolerance between groups. Exercise is well known to increase skeletal muscle oxidative capacity McKie et al, 2019;Stanford, Middelbeek, & Goodyear, 2015) and in the current study, we observed consistent exercise-induced increases in the protein content of HKII (p < .001), CYTO C, COX IV, and PGC1α (p < .05; Figure 1e) in the triceps muscle.…”
Section: Days Of Vwr Exercise Training Attenuates Weight Gain Desupporting
confidence: 85%
“…Results of the GTT (Figure 1d) indicated a nonsignificant trend (p = .052) in glucose tolerance between groups. Exercise is well known to increase skeletal muscle oxidative capacity McKie et al, 2019;Stanford, Middelbeek, & Goodyear, 2015) and in the current study, we observed consistent exercise-induced increases in the protein content of HKII (p < .001), CYTO C, COX IV, and PGC1α (p < .05; Figure 1e) in the triceps muscle.…”
Section: Days Of Vwr Exercise Training Attenuates Weight Gain Desupporting
confidence: 85%
“…This study has a potential limitation: Recent work (McKie et al, 2019;Raun et al, 2020) has demonstrated that housing mice at subthermal neutral conditions, that is, room temperature, rather than at thermal neutrality can stimulate increases in mitochondrial and thermogenic proteins in adipose tissues with endurance exercise training. Housing temperature (22-24°C) may have impacted our data because the thermoneutral zone of Wistar rats is in the range of 29.5-30.5°C (Romanovsky, Ivanov, & Shimansky, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, the total running distance completed at 29°C was still ∼20% higher ( P = 0.0614) after the intervention (McKie et al . ). However, the time spend on the wheel was the same at both temperatures, so the mice housed in thermoneutral conditions must have been running at a higher intensity.…”
Section: Perspectivesmentioning
confidence: 97%
“…In a recently published paper in The Journal of Physiology , McKie et al . () undertook a detailed description of the importance of housing temperature in exercise training‐induced adaptations of adipose tissue in mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation